Development of e-commerce in the context of digitalization - S. K. Yeshugova; S. K. Khamirzova (Новые технологии)
In the context of digitalization, there is a rapid growth of e-commerce, so it is a relevant issue. This implies the need to improve digital technologies, develop Internet platforms, set up sales channels and Internet marketing tools for promotion on the online market in order to obtain the planned profit. The subject of the research is organizational and managerial relations and processes that arise in enterprises working in the field of online marketing and e-commerce. The purpose of the research is to substantiate the role and place of e-commerce in the context of digitalization, as well as to analyze the state of the e-commerce market in modern conditions. The article reveals the ever-in- creasing role of e-commerce in the innovative modernization of the Russian economy; substantiates the need for widespread use of Internet marketing opportunities in order to attract consumers of goods and services, as well as market partners for the implementation of business projects. An analysis of the scale of e-commerce has showed that in recent years, the Russian e-commerce market has grown by an average of 29% per year, reaching 2,06 trillion rub. by 2019 in the total volume. Organization of electronic commerce in the market involves the implementation of a number of stages: analysis of the market situation; selection of e-commerce channels, ensuring the effectiveness of sales; controlling and evaluating the effectiveness of online trading. At present, various types of Internet platforms are currently used: stock exchanges, corporate sites, forums and industry clubs, landing pages, informa- tion blogs and magazines, trading platforms, rubrics, bulletin boards, etc., depending on the specific characteristics, features and promotion tools. It has been concluded that the prospects for the devel- opment of e-commerce in modern conditions are associated with the need to develop digital technol- ogies, overcome the digital divide, as well as the integration of small and medium-sized enterprises into the global Internet space.